The comparison of the effects of a novel hydrogel compound and traditional hyaluronate following micro-fracture procedure in a rat full-thickness chondral defect model - Yunus Emre Akman; Erhan Sukur; Ahmet Senel; Nur Ece Oztas Sukur; Canan Kelten Talu; Yusuf Ozturkmen (Acta Orthopaedica et Traumatologica Turcica, 2017)
Purpose: The aim of this experimental study was to investigate the impact of HA–CS–NAG compound (hyaluronate, sodium chondroitin sulfate, N-acetyl-d-glucosamine) on the quality of repair tissue after micro-fracture and to compare it with HA (hyaluronat), in a rat full-thickness chondral defect model. Methods: Full-thickness chondral defects were created in a non-weight bearing area by using a handle 2.7-mm drill bit, in the right knees of 33 Sprague–Dawley rats. Each specimen then underwent micro-fracture using a needle. Two weeks after surgery, 3 groups were randomly formed among the rats (n = 33). In Group 1, 0.2 mL of sterile saline solution (0.9%) was injected. In Group 2, 0.2 mL HA with a mean molecular weight of 1.2 Mda was injected. In Group 3, 0.2 mL of HA–CS–NAG compound (hyaluronate, sodium chondroitin sulfate, N-acetyl-d-glucosamine) was injected. The injections were applied on the 14th, the 21st and the 28th postoperative days. All rats were sacrificed on the 42nd postoperative day. Histological analysis of the repair tissue was performed for each specimen by two blinded observers using Wakitani scoring system. Results: There was significantly improved repair tissue in both Group 3 and Group 2 when compared with Group 1. Group 3 showed statistically significant improvement in terms of ‘cell morphology’ and ‘integration of donor with host’ when compared to Group 2 (p < 0.001). Conclusion: Intra-articular injection of HA–CS–NAG compound after micro-fracture results in significantly improved repair tissue in rats' chondral defects when compared to HA regarding the donor integration and cell morphology. Keywords: Cartilage lesion, Micro-fracture, Hyaluronate, Chondroitin sulfate, N-acetyl-d-glucosamine